Finding Healing and Balance in Learning and Teaching at the First Nations University of Canada - Faith, Erika (First Peoples Child & Family Review, 2007)
In this personal memoir of three years teaching at the First Nations University of Canada, the author reﬂects on what she learned, in applying internally and externally, an Aboriginal model of social work education. As a person of non-Aboriginal ancestry, she explores how her own struggle with the imbalances inherent in academia spurred her search in grounding her teaching in holism, healing, reciprocal relationships, empowerment, liberation, and pleasure, and how the integration of these practices strengthened her relationships with her own spirit, but also with ‘all my relations’.